1994
DOI: 10.1093/carcin/15.2.331
|View full text |Cite
|
Sign up to set email alerts
|

H-ras 61st codon activation in archival proliferative hepatic lesions isolated from female B6C3F1 mice exposed to the leukotriene D4-antagonist, LY171883

Abstract: LY171883, a peroxisome proliferator and leukotriene D4-antagonist, induced a statistically significant increase in the number of hepatic lesions in B6C3F1 female mice in a 2 year oncogenicity study at dietary doses of 0.0225% and 0.075%. The mutation frequency and spectrum of the 61st codon of H-ras was determined for 64 independent, archived lesions from the LY171883 2 year oncogenicity study using the polymerase chain reaction (PCR), allele specific oligo hybridization (ASO) and DNA sequencing. Results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The H-ras oncogene point mutation in codon 61, a CAA to AAA transversion (G to T in the nontranscribed strand), is the principal ras-oncogene mutation occurring in both spontaneous and carcinogen-induced B6C3F 1 mouse liver tumors [61][62][63][64][65][66][67][68]. Using enzymatic amplification and confirmation by direct sequencing [69], we have also shown that the liver tumors induced in the neonatal B6C3F 1 mouse by the human aromatic amine carcinogen, 4-aminobiphenyl (4-ABP), had a high proportion (16/16) of the same specific codon 61 mutation (CAA to AAA) in the H-ras oncogene (Table 3).…”
Section: B Induction Of Ras-protooncogene Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The H-ras oncogene point mutation in codon 61, a CAA to AAA transversion (G to T in the nontranscribed strand), is the principal ras-oncogene mutation occurring in both spontaneous and carcinogen-induced B6C3F 1 mouse liver tumors [61][62][63][64][65][66][67][68]. Using enzymatic amplification and confirmation by direct sequencing [69], we have also shown that the liver tumors induced in the neonatal B6C3F 1 mouse by the human aromatic amine carcinogen, 4-aminobiphenyl (4-ABP), had a high proportion (16/16) of the same specific codon 61 mutation (CAA to AAA) in the H-ras oncogene (Table 3).…”
Section: B Induction Of Ras-protooncogene Activationmentioning
confidence: 99%
“…mutations were observed in the K-ras or N-ras oncogenes. During development of liver tumors, ras-oncogene activation occurs during focus formation, as well as at later stages (e.g., during adenoma and carcinoma formation) [67].…”
Section: B Induction Of Ras-protooncogene Activationmentioning
confidence: 99%
“…These sequence alterations in the ras-protooncogenes frequently reflect the mutational specificity of the carcinogen (63,64). It has been found that rus-oncogene activation occurs both at an early stage (eg, during focus formation) as well as at later stages of liver tumor development (eg, during adenoma and carcinoma formation) (65).…”
Section: Rus-protooncogene Activationmentioning
confidence: 99%
“…A CAA to AAA transversion (G to T in the nontranscribed strand), in particular, is the principal H-rus point mutation in codon 61 occurring in both the spontaneous and the carcinogen-induced B6C3Fl mouse liver tumors (59,62,(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
Section: Rus-protooncogene Activationmentioning
confidence: 99%
“…Most published tumor ras mutational profiles originate from tumors induced in the B6C3F 1 hybrid mouse. With only a few exceptions, it has been found that point mutation in codon 61 of H-ras is the principal ras-oncogene mutation in these tumors (10)(11)(12). The results from our studies on PAHs and their derivatives represent a major exception and may indicate a chemical-class specificity for these mutations.…”
Section: Discussionmentioning
confidence: 47%